Umur dan Ukuran Perusahaan Memoderasi Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan - Yudha, Nyoman Tryadi Kusuma; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 32 No 3 (2022)DO - 10.24843/EJA.2022.v32.i03.p03, 2022)
This study aims to determine the effect of corporate social responsibility on firm value moderated by age and firm size. Stakeholder theory, signaling theory and legitimacy theory are used as the theoretical basis. The number of samples obtained as many as 25 companies with purposive sampling technique. The analysis technique used is Moderated Regression Analysis (MRA). The results of the research analysis show that the type of moderation is quasi moderation which indicates that corporate social responsibility has a positive effect on firm value, age and firm size can moderate the effect of corporate social responsibility on firm value. The implication of this research is that it can provide investors with an overview of the company's performance which is reflected in the annual report so that they can make the right decisions. Keywords:  Company Age; Company Size; Corporate Social Responsibility; Firm Value.